Minimax Theorem for Two Set-Valued Mappings with Nonconvex Domains. (23rd August 2021) - Zhang, Qing-bang
Abstract: In this paper, we obtain the operational properties of the set MaxA ( MaxW A, MinA and MinW A ) of a set A in the sense of vector optimization and its' applications to the judgment of the convexity and concavity of a set-valued mapping. By using the separation theorem of convex sets, some minimax theorems of two set-valued mappings have proved in the nonconvex sets. Simultaneously, two examples are given to show our results.